1995
DOI: 10.1002/art.1780380914
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of systemic lupus erythematosus race and gender differences

Abstract: Objective. To examine racial differences in the incidence of systemic lupus erythematosus (SLE).Methods. A population-based registry of SLE patients in Allegheny County, Pennsylvania, was used to identify incident cases of SLE diagnosed between January 1, 1985 and December 31, 1990, from 3 sources, by medical record review (University of Pittsburgh Lupus Databank, rheumatologists, and hospitals). Capture recapture methods using log-linear models were used to estimate the level of case-finding and to calculate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
246
5
13

Year Published

1996
1996
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(277 citation statements)
references
References 36 publications
13
246
5
13
Order By: Relevance
“…Our observation that African-Americans carry fewer CRP low alleles than Caucasians might initially seem at odds with this hypothesis, as African-Americans are known to have a disproportionately higher incidence of SLE. 41 However, if CRP contributes to the pathogenesis of SLE at all, it likely acts as a disease modifying factor rather than a disease risk factor. This could explain the preferential association of Fc␥RIIa alleles (a CRP receptor) with SLE in African-Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that African-Americans carry fewer CRP low alleles than Caucasians might initially seem at odds with this hypothesis, as African-Americans are known to have a disproportionately higher incidence of SLE. 41 However, if CRP contributes to the pathogenesis of SLE at all, it likely acts as a disease modifying factor rather than a disease risk factor. This could explain the preferential association of Fc␥RIIa alleles (a CRP receptor) with SLE in African-Americans.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we have not reported on mitotic indices in the tissues under investigation, nor data on the recruitment/retention/ phenotype of lymphoid cells-this work is currently in progress. Lupus disease develops in nine times more women than men [29,30], and this trend is echoed in mice [31]. Sex hormones can substantially affect development of the disease in mouse, with androgens protecting males resulting in prevalence of the syndrome in females [23].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with Caucasians, the prevalence of SLE is higher among North American Indians, African-Americans, African-Caribbeans, Hispanics and Asians. [8][9][10][11]19,[26][27][28][29][30] In IA, the reported prevalence of SLE varies from 52.6 to 92.8 per 100 000 people, a prevalence two to four times higher than that of Caucasians (Table 1). [12][13][14][15][16] In Far North Queensland, SLE prevalence in IA was 92.8 per 100 000 persons, twice that of the generally European descended population (45.3 per 100 000 persons).…”
Section: Sle In Indigenous Australiansmentioning
confidence: 99%